The Log Data Collection Service for Cloud Robotics - Liman, Dmitry A.; Shustova, Larisa I.; Chugunkov, Ilya V.; Dyumin, Alexander A. (2017 IEEE 11th International Conference on Application of Information and Communication Technologies (AICT), 2017)
Mobile robotic systems became essential part of our daily life. They can interact with humans as valued helpers, sometimes in relatively sophisticated tasks, which makes it necessary to record as much information as possible about robotic device activities. But if common approaches are used for data fixation in storage system, some portions of the data can be lost due to network constraints and/or robotic device failures. The paper discusses the log service architecture that provides reliable log delivery to the central storage from distributed heterogeneous mobile robotic nodes. Proposed log system consists of logical entities performing log buffering at robotic nodes, log transfer and centralized log data storage. Variety of log data types, generated by robotic nodes, are discussed, as well as the peculiarities of data storage. The necessity of data transmission between nodes is emphasized and the log data transmission algorithm is described.